Transient Nonlinear Response of Impulsively-Loaded Circular Plates - Tuomala, M.T.E.; Mikkola, M.J. (Engineering Transactions, 1981)
The finite element procedure used in this study is based on the incremental Lagrangian approach. Geometrical nonlinearity is included. The elastic viscoplastic material model is adopted in a form suitable for large strains. Linear 2-noded and parabolic 3-noded isoparametric axisymmetric shell elements are employed. Numerical time integration is carried out by the central difference scheme. The agreement between computed and experimental results is at least satisfactory. The discrepancies can be explained by combined effects of smalt inaccuracies of loading geometry, constitutive parameters, boundary conditions, and numerical discretization and round-off errors.